Pathogenic mechanisms underlying spinocerebellar ataxia type 1 - Tejwani, Leon (Cell Mol Life Sci, 2020)
The family of hereditary cerebellar ataxias is a large group of disorders with heterogenous clinical manifestations and genetic etiologies. Among these, over 30 autosomal dominantly inherited subtypes have been identified, collectively referred to as the spinocerebellar ataxias (SCAs). Generally, the SCAs are characterized by a progressive gait impairment with classical cerebellar features, and in a subset of SCAs, accompanied by extra-cerebellar features. Beyond the common gait impairment and cerebellar atrophy, the wide range of additional clinical features observed across the SCAs is likely explained by the diverse set of mutated genes that encode proteins with seemingly disparate functional roles in nervous system biology. By synthesizing knowledge obtained from studies of the various SCAs over the past several decades, convergence onto a few key cellular changes, namely ion channel dysfunction and transcriptional dysregulation, has become apparent and may represent central mechanisms of cerebellar disease pathogenesis. This review will detail our current understanding of the molecular pathogenesis of the SCAs, focusing primarily on the first described autosomal dominant spinocerebellar ataxia, SCA1, as well as the emerging common core mechanisms across the various SCAs.